Telemedicine dan Kesehatan: Memahami Dampak Teknologi Kedokteran di Era Digital dalam Konteks Ajaran Islam - Nur Ismiyah; Aura Malika Asy-Syifa (Jurnal Medika Nusantara, 2024)
In the digital era, telemedicine has revolutionized healthcare by providing faster and more accessible remote medical services. This article explores the transformative impact of this technology on the quality and accessibility of healthcare services, while also examining its compatibility with Islamic values. From an Islamic perspective, telemedicine is reviewed in relation to ethical principles such as the preservation of life, the ease of access to treatment, and respect for patient privacy. The article aims to highlight how telemedicine can serve as an innovative solution that not only supports modern healthcare advancements but also aligns with ethical guidelines within Islamic teachings. This study offers fresh insights into the opportunities and challenges of telemedicine in healthcare, particularly within Muslim communities, and its implications for ethical medical decision-making.